Kepatuhan minum obat hipoglikemik oral dan indeks massa tubuh terhadap kadar gula darah pada pasien diabetes melitus tipe 2 - Wathani, Ika Hanna Nurul; Purba, Martalena Br; Helmyati, Siti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2024)
Adherence to oral hypoglycemic drugs and body mass index on blood sugar level in patients with type 2 diabetes mellitusBackground: Type 2 Diabetes mellitus (T2DM) is the most common diabetes and more than 95% of people with diabetes have type 2 diabetes mellitus. The Special Region of Yogyakarta is the province with the second highest prevalence of DM in Indonesia. One of the obstacles that often occurs in patients with T2DM who require long-term therapy is non-adherence to treatment and lack of attention to nutritional status which has an impact on the blood sugar levels of patients with T2DM.Objective: This study aims to analyze the relationship between the level of adherence to oral hypoglycemic drugs and body mass index on blood sugar levels in patients with T2DM in the working area of Minggir Health Center. Methods: A cross-sectional study design with purposive sampling technique. Obtained a total of 96 patient with T2DM in October 2023 who had met the inclusion and exclusion criteria, including using oral hypoglycemic drugs for at least 6 months and not using insulin therapy. Data on adherence to oral hypoglycemic drugs were obtained using the MARS-5 questionnaire, data on blood sugar levels used fasting blood sugar levels, and body mass index values were obtained from measuring height and weight. The analysis used the Chi-square test (p-value<0,05).Results: The majority of respondents had a high level of adherence to oral hypoglycemic drugs (56,3%), were overweight (79,2%), and had poor blood sugar levels (55,2%). There was no significant relationship between the level of adherence to oral hypoglycemic drugs and blood sugar levels ((P-value=0,776; PR=0,912). A non-significant relationship was also found between body mass index and blood sugar levels ((P-value=1,000; PR=1,005).Conclusions: The level of adherence to oral hypoglycemic drugs and body mass index were not significantly associated with blood sugar levels in patients with T2DM